2016
DOI: 10.1016/j.ultras.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Mode & mechanism of low intensity pulsed ultrasound (LIPUS) in fracture repair

Abstract: It has been 30years since the first level one clinical trial demonstrated low intensity pulsed ultrasound (LIPUS) could accelerate fracture repair. Since 1994 numerous investigations have been performed on the effect of LIPUS. The majority of these studies have used the same signal parameters comprised of an intensity of 30mW/cm(2) SATA, an ultrasound carrier frequency of 1.5MHz, pulsed at 1kHz with an exposure time of 20minutes per day. These studies show that a biological response is stimulated in the cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
108
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 48 publications
1
108
1
2
Order By: Relevance
“…In accordance with the proposed mechanism for how LIPUS stimulation works in vivo (Harrison et al, 2016), we show that integrin-mediated cell-ECM adhesions are essential for the cellular responses to LIPUS (Fig. 4), and that vinculin has a critical role in this process (Fig.…”
Section: Mechanical Stimulation By Lipus Is Sensed By Vinculin At Fassupporting
confidence: 87%
See 3 more Smart Citations
“…In accordance with the proposed mechanism for how LIPUS stimulation works in vivo (Harrison et al, 2016), we show that integrin-mediated cell-ECM adhesions are essential for the cellular responses to LIPUS (Fig. 4), and that vinculin has a critical role in this process (Fig.…”
Section: Mechanical Stimulation By Lipus Is Sensed By Vinculin At Fassupporting
confidence: 87%
“…Previous reports showed that the 200 ms pulses produce nano-vibrations (Argadine et al, 2005;Harrison et al, 2016) as well as acoustic pressure (Fung et al, 2014), exposing cells to rapid mechanical stimuli.…”
Section: Mechanical Stimulation By Lipus Is Sensed By Vinculin At Fasmentioning
confidence: 99%
See 2 more Smart Citations
“…LIPUS was previously demonstrated to promote bone formation and accelerate bone maturation in cases of bone fracture (6,7), distraction osteogenesis (8) and delayed fracture union (9). LIPUS appears to act by affecting the biological mechanisms of cell proliferation, gene regulation and cell differentiation (10).…”
Section: Introductionmentioning
confidence: 99%